A PREDICTIVE MODEL FOR AXILLARY LYMPH NODE PATHOLOGIC COMPLETE RESPONSE IN PREMENOPAUSAL BREAST CANCER PATIENTS AFTER NEOADJUVANT CHEMOTHERAPY: A CROSS-SECTIONAL STUDY IN A L ATIN-AMERICAN POPULATION - Duque, Carolina Benavides; Pérez, Luis Fernando Zapata; Zapata, Ana María Fidalgo; López, Laura; Vásquez, Elsa; López, Javier Cuello (Mastology, 2018)
Introduction: A large group of lymph node-positive breast cancer patients receive neoadjuvant chemotherapy and subsequently undergo axillary lymph node dissection. It has been previously proposed that axillary lymph node dissection may be avoided — and it’s associated reduced morbidity — in patients showing pathologic complete response. Therefore, the purpose of this study was to develop a nomogram to predict axillary node pathologic response to neoadjuvant chemotherapy in breast cancer patients in order to guide the surgical treatment decision-making process for this group of patients. Methods: A cross-sectional, secondary data study was carried out between 2013-2016 on 222 lymph node-positive breast cancer patients who received neoadjuvant chemotherapy followed by locoregional management, including axillary lymph node dissection. Logistic regression analysis was performed to determine the association of the axillary pathologic complete response with the different clinical and pathological variables. Variables found to be statistically significantly associated with axillary pCR (pathologic complete response) were used to create the logistic regression model and the nomogram in pre-menopausal patients. Axillary pCR was defined as absence of residual disease in the breast and of micro-metastasis in axillary lymph nodes. Samples with isolated tumor cells were considered as positive for residual disease. Results: a total of 222 patients were included, of which 131 were premenopausal at the time of diagnosis. Axillary pathologic complete response was observed in 55.7% (73 of 131) of patients, and was significantly associated with estrogen receptor (ER) negative tumors (OR 2.59, 95%CI 1.21-5.53), progesterone receptor (PR) negative tumors (OR 2.63, 95%CI 1.28-5.38), and Her2 positive tumors (OR 0.40, 95%CI 0.19-0.84), for which a significant correlation with increased probability of achieving axillary pathologic complete response was evidenced. Conclusion: The performance of this model to predict axillary pCR in pre-menopausal patients was weak, and therefore the decision to avoid surgical axillary dissection should not be based solely on the developed nomogram. However, further studies may lead to validation of this model.